GAMBARAN TINGKAT KECEMASAN PADA PASIEN KANKER PAYUDARA PRE OPERASI DI RSUP DR. M. DJAMIL PADANG 2025 - Syach Fatih Malikul Mulki; Mutiara Anissa; Budi Yulhasfi Febrianto; Rialta Hamda; Tia Reza (Yayasan Nusantara Hasana Berdikari, 2025)
Breast cancer is the most common type of cancer affecting women and often requires surgical management. Surgical procedures frequently cause anxiety in patients, which can impact the healing process and the effectiveness of treatment. High levels of preoperative anxiety may negatively affect patients’ physiological and psychological conditions. This study aims to describe the level of anxiety in breast cancer patients before undergoing surgery at RSUP Dr. M. Djamil Padang. This research is a descriptive categorical study using purposive sampling. The sample consisted of 59 breast cancer patients scheduled for surgery at the Oncology Clinic & Inpatient Ward 1 Day Before Surgery at RSUP Dr. M. Djamil Padang, who met the inclusion and exclusion criteria. The instrument used was the APAIS (Amsterdam Preoperative Anxiety and Information Scale) questionnaire. The majority of patients scheduled for surgery at RSUP Dr. M. Djamil Padang were over 45 years old (76.3%), had completed senior high school (49.2%), were unemployed (71.2%), and most had never undergone surgery before (59.3%). Anxiety levels showed that 40.7% of patients experienced mild anxiety, 37.3% moderate anxiety, and 22% severe anxiety. No patients experienced very severe (panic-level) anxiety. Most breast cancer patients in the preoperative phase at RSUP Dr. M. Djamil Padang experienced mild to moderate anxiety. These findings highlight the importance of providing education and psychological support to patients prior to surgery.